Scaffolding Based on Problems in Graph Theory Learning - Yunita Oktavia Wulandari; Nia Wahyu Damayanti (International Journal of Trends in Mathematics Education Research, 2018)
Scaffolding is assistance provided so students can solve problems or understand concepts that can not be solved independently. When students are considered capable of completing their tasks independently, the assistance is eliminated. In this study, scaffolding was carried out by giving problems about graph theory. Problems given are closed and open contextual problems. The selection of this problem can be seen by students' understanding of graph theory. The results of this study, this problem-based scaffolding can help students who experience difficulties in the problem of graph theory. Students are enthusiastic because through this problem, they can explore and connect blood donation problems and regional tourism with the concept of graph.